Inverse problem of electrocardiography - Lairenjam, Benaki; Satyendra Singh, Satyendra (International Journal of Engineering and Technology, 2019)
Inverse problem in Electrocardiography (ECG) is the mathematical formulation of the electrical activity of the heart surface from the measured body surface potential. This paper presents a state of art review of the inverse problem in ECG and the recent development in the solution of the mathematical model.Â Â